2018
DOI: 10.4244/eij-d-17-00947
|View full text |Cite
|
Sign up to set email alerts
|

National trends, predictors of use, and in-hospital outcomes in mechanical circulatory support for cardiogenic shock

Abstract: In-hospital mortality for CS has declined but remains high. Rates of CS have outpaced MCS utilisation which remains uncommon in non-MI hospitalisations with shock. MCS is associated with utilisation of other procedures during hospitalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 29 publications
2
41
2
Order By: Relevance
“…With the exception of the IMPRESS-in-Severe-SHOCK trial, which included younger patients, the age of included patients in previous RCTs of active MCS was similar to the present study [14,[22][23][24]. On the other hand, previous cohort studies showed a lower age of patients receiving active MCS, which might be due to selection bias [17,27,31,32]. The shock index, which was identified as a strong outcome predictor in STEMI patients, was higher in patients receiving active MCS [33].…”
Section: Clinical Characteristics and Rates Of Mcs Implementationsupporting
confidence: 75%
“…With the exception of the IMPRESS-in-Severe-SHOCK trial, which included younger patients, the age of included patients in previous RCTs of active MCS was similar to the present study [14,[22][23][24]. On the other hand, previous cohort studies showed a lower age of patients receiving active MCS, which might be due to selection bias [17,27,31,32]. The shock index, which was identified as a strong outcome predictor in STEMI patients, was higher in patients receiving active MCS [33].…”
Section: Clinical Characteristics and Rates Of Mcs Implementationsupporting
confidence: 75%
“…To date, the Intra-aortic Balloon Pump (IABP)-SHOCK II trial is the only adequately powered randomised controlled trial assessing the use of MCS in AMICS, and the trial failed to show any prognostic benefit with the use of IABP 3. Contemporary studies on temporal trends in use of MCS in AMICS are limited but generally show a shift in choice of the device with a decrease in the use of IABP and an increase in the use of other devices, namely, venoarterial extracorporeal membrane oxygenation (VA-ECMO) and transvalvular microaxial flow pumps 4 5. In a recent retrospective study, general use of Impella was not associated with improved survival compared with the IABP 6.…”
Section: Introductionmentioning
confidence: 99%
“…Use of ECMO has been increasing both nationally(1-4) and internationally, (5) particularly in the setting of cardiogenic shock (CS). (4,6) While ECMO can provide rapid stabilization of the patient in extremis, it remains a morbid (7)(8)(9) and resource-intensive therapy. (10) Appropriate selection of patients who could derive the greatest benefit from this therapy remains a challenge prompting ongoing efforts to identify determinants of outcomes.…”
Section: Introductionmentioning
confidence: 99%